Taxing and trading carbon emissions in the EU: Distributional comparisons of mixed policies - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
We model EU-type carbon emissions control in a group of countries to explore the distributional incidence of mixed policies that consist of an emissions trading scheme (ETS) and of emissions taxes overlapping with the ETS. Such policies impact on national welfares through both the overlapping taxes and the distribution of national emissions caps. Our main proposition is an equivalence result stating that for every mixed policy, there exists an ETS policy without overlapping taxes yielding the same levels of national welfare as the mixed policy. We also suggest two measures of the net distributional incidence of mixed policies.
Keywords: H23; Q52; 330; emissions cap; emissions tax; emissions trading; Kohlendioxid; Klimaschutz; Policy-Mix; Ökosteuer; Emissionshandel; Wirkungsanalyse; Wohlfahrtseffekt